2012
DOI: 10.1074/jbc.r111.270678
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Disulfide Relay: Redox-regulated Protein Import into the Intermembrane Space

Abstract: 99% of all mitochondrial proteins are synthesized in the cytosol, from where they are imported into mitochondria. In contrast to matrix proteins, many proteins of the intermembrane space (IMS) lack presequences and are imported in an oxidation-driven reaction by the mitochondrial disulfide relay. Incoming polypeptides are recognized and oxidized by the IMSlocated receptor Mia40. Reoxidation of Mia40 is facilitated by the sulfhydryl oxidase Erv1 and the respiratory chain. Although structurally unrelated, the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 101 publications
0
98
0
Order By: Relevance
“…Mia40 is a receptor, folding catalyst, and disulfide carrier, and the Erv1 protein serves as a sulfhydryl oxidase. The oxidative folding is believed to provide a trapping mechanism that prevents the escape of proteins from the IMS back to the cytosol (10,13,18). Our initial result raised a possibility that the reverse process can also occur, as we observed the relocation of in vitro imported Tim8 from mitochondria to the incubation buffer (13).…”
mentioning
confidence: 70%
“…Mia40 is a receptor, folding catalyst, and disulfide carrier, and the Erv1 protein serves as a sulfhydryl oxidase. The oxidative folding is believed to provide a trapping mechanism that prevents the escape of proteins from the IMS back to the cytosol (10,13,18). Our initial result raised a possibility that the reverse process can also occur, as we observed the relocation of in vitro imported Tim8 from mitochondria to the incubation buffer (13).…”
mentioning
confidence: 70%
“…To examine whether this modification influenced binding, we performed experiments in which the energy donor Trp was placed in Mia40 and the acceptor AEDANS in Cox17*. Four single-cysteine variants of Cox17* were produced and labelled with AEDANS (variants [8][9][10][11]. Their interaction with the wild-type form of Mia40 was then measured in equilibrium titrations, and its kinetics was followed in the stopped-flow instrument by the FRET between the single Trp (W294) of Mia40 and the AEDANS groups of the four Cox17* variants ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the sliding-and-docking model 22 cannot readily account for the formation of the second disulphide in CX 3 C and CX 9 C substrates of Mia40, because the hydrophobic residues of the MISS/ITS motif become buried at the helix interface during folding and are thus no longer available for Mia40 to introduce the second disulphide. To remedy this situation, it was suggested that the second disulphide forms spontaneously independent of Mia40 by reaction with GSSG or with oxygen 11,23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations